Transformasi Teknologi untuk Memperkuat Kreativitas dan Seni Anak dalam Mendukung Pembelajaran TIK di Sekolah - Amaliati, Siti; Maani, Arifatul; Fauziah, Fauziah (Journal of Community Sustainability, 2024)
This Community Service (PkM) activity aims to develop children's creativity and art skills through the introduction of information and communication technology (ICT), especially the use of Microsoft Paint applications. This activity was carried out at Teras Literasi Gresik by involving elementary school children as the main subjects. The program is designed to integrate technology learning with art experiences, so that children not only understand the theory, but also practice directly the features of Paint such as drawing, coloring, and editing images. A practice-based approach is applied to improve children's digital skills early on, while familiarizing them with using computer software in a fun and applicable way. The implementation results showed that participants were active and enthusiastic in participating in the activities, although some still needed assistance to operate the device. question and answer session at the end of the activity showed the participants' increased understanding of the material taught. Limited facilities, such as the number of devices available, became a major challenge in this activity, but did not reduce the overall effectiveness of the program. This activity succeeded in creating an interactive learning atmosphere, improving digital literacy, and preparing children to adapt to more complex technologies in the future. This program makes a real contribution to the development of children's digital and artistic skills in the context of basic education